Analysis of creative thinking ability in implementing the PBM-B3 Model - Monalisa Sinaga; Bornok Sinaga; Waminton Rajagukguk (Himpunan Pengembang Kurikulum Indonesia, 2025)
Indonesian students' low creative thinking ability at both international and national levels highlights the need for further efforts to improve the quality of mathematics education in Indonesia. This research aims to describe the level of students' mathematical creative thinking abilities and students' difficulties in completing students' mathematical creative thinking ability tests after implementing the Batak Culture Problem-Based Mathematics Learning model (PBM-B3). This research is a qualitative descriptive research. The subjects of this research were fourth-grade students at SD Negeri 030280 Sidikalang. In contrast, the object of this research was the ability to think creatively in mathematics in applying the PBM-B3 model. The research results indicate that students' mathematical creative thinking abilities improved after implementing the PBM-B3 model compared to conventional methods. Most students fall into the medium category, while very high, high, and low categories represent smaller percentages. Indicator analysis shows fluency in the high category, flexibility and elaboration in the medium category, and originality in the low category. Students in the very high category excelled across all indicators. In contrast, those in the high category faced difficulties with principles, while those in the medium and low categories struggled with principles and procedures. Abstrak Rendahnya kemampuan berpikir kreatif peserta didik Indonesia di tingkat internasional maupun nasional menyoroti perlunya upaya lebih lanjut dalam meningkatkan kualitas pendidikan Matematika di Indonesia. Penelitian ini bertujuan untuk mendeskripsikan tingkat kemampuan berpikir kreatif matematis peserta didik dan kesulitan peserta didik dalam menyelesaikan tes kemampuan berpikir kreatif matematis peserta didik setelah pelaksanaan model Pembelajaran Matematika Berdasarkan Masalah Berbasis Budaya Batak (PBM-B3). Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah peserta didik kelas IV SD Negeri 030280 Sidikalang, sedangkan objek dalam penelitian ini adalah kemampuan berpikir kreatif matematis dalam penerapan model PBM-B3. Hasil penelitian menunjukkan bahwa kemampuan berpikir kreatif matematis peserta didik meningkat setelah penerapan model PBM-B3 dibandingkan pembelajaran konvensional. Sebagian besar peserta didik berada pada kategori sedang, sementara kategori sangat tinggi, tinggi, dan rendah memiliki persentase yang lebih kecil. Analisis indikator menunjukkan kelancaran berada pada kategori tinggi, fleksibilitas dan elaborasi di kategori sedang, serta orisinalitas di kategori rendah. Peserta didik kategori sangat tinggi unggul dalam semua indikator, sedangkan kategori tinggi mengalami kesulitan pada prinsip, dan kategori sedang serta rendah mengalami kesulitan pada prinsip dan prosedur. Kata Kunci: budaya Batak; kemampuan berpikir kreatif; PBM-B3; pembelajaran Matematika berbasis masalah